ANALISIS KESULITAN SISWA DALAM MENEMUKAN INFORMASI PENTING DARI SEBUAH BACAAN PARAGRAF - Eka Nur Oktafiani; Dedy Irawan (Jurnal Muara Pendidikan, 2021)
Indonesian is a compulsory subject at all levels of education in Indonesia. Difficulties in learning Indonesian are the difficulties experienced by students in both low and high grades. This study aims to (1) find out the difficulties of students in finding important information from a paragraph reading in class V SD N 2 Dukuhwaluh (2) find out the factors that cause students to have difficulty in finding important information from a paragraph reading.This research is a qualitative descriptive research with case study method. Data collection techniques by means of observation, interviews and documentation analysis. Data analysis techniques from data reduction, data presentation and verification. The results showed that there were two students who had difficulty in finding important information from a paragraph reading in class V SD N 2 Dukuhwaluh